PENGARUH LOKASI PENJUALAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PETERNAKAN AYAM RAS PEDAGING ( BROILER ) KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Rizky Wiya Ningsih; Nilawati Nasti; Syafrizal . (Universitas Islam Islam Sumatera Utara, 2021)
The formulation of the problem in this study is whether the location of the sale affects the consumer's purchase decision, whether the price affects the consumer's purchase decision, whether the location of the sale and the price affect the consumer's purchase decision. The purpose of this study is to know the influence of sales location on consumer purchasing decisions, To know the influence of prices on consumer purchasing decisions, To know the influence of sales locations and prices on consumer purchasing decisions. This research is a survey research and is casual associative. The population in this study amounted to 100 people and the sample in this study amounted to 100 buyers on broiler breed chickens. Data collection techniques using questionnaires that have been tested for validity and reliability. Tenik data analysis used is multiple linear regression. The results of this study show that Sales Locations have a positive and significant effect on consumer purchasing decisions. This is evidenced by the calculated t value the table t value of 2,681 1,984 with a significant rate of 0.000 0.05. Price has a positive and significant effect on consumer purchasing decisions, This is evidenced by the calculated t value of t table which is 7,377 1,984 with a significant rate of 0.000 0.05 Sales Location and Price positively and significantly affect consumer purchasing decisions. This is evidenced by the value of f calculate f table which is 61,134 3.09 with a significant rate of 0.000 0.05.